1992
DOI: 10.1210/jcem.75.1.1619014
|View full text |Cite
|
Sign up to set email alerts
|

Postparathyroidectomy transient thyrotoxicosis.

Abstract: Three patients are described who had spontaneously resolving transient thyrotoxicosis after resection of a parathyroid adenoma without thyroidectomy or an apparent thyroid abnormality before or during surgery. All had documented thyrotoxicosis that developed within 2 weeks after surgery, which was clinically symptomatic in two of three patients. The thyrotoxicosis was associated with subnormal radioactive iodine thyroid uptake when performed in the two symptomatic patients and was consistent with a postsurgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…In these reports, it was suggested that the acute reduction in glucocorticoid may have exacerbated a subclinical thyroiditis. Postparathyroidectomy thyrotoxicosis was also reported, and thyroid autoantigen release during surgery was suggested as a cause of this case [4]. In our case, the surgery was for an FSH-producing pituitary adenoma.…”
Section: Discussionmentioning
confidence: 51%
“…In these reports, it was suggested that the acute reduction in glucocorticoid may have exacerbated a subclinical thyroiditis. Postparathyroidectomy thyrotoxicosis was also reported, and thyroid autoantigen release during surgery was suggested as a cause of this case [4]. In our case, the surgery was for an FSH-producing pituitary adenoma.…”
Section: Discussionmentioning
confidence: 51%
“…1) TSAb may have stimulated the metastatic carcinoma to develop thyrotoxicosis in the patient. Development of Graves' disease has been described following parathyroidectomy [11], radioiodine therapy [12], acute and subacute thyroiditis [13] and in patients treated with a percutaneous ethanol injection (PEI) [14]. Before the remnant thyroidectomy at the previous hospital, TRAb was positive and remained stable after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The serum level of Tg is frequently increased after aspiration of the thyroid [20]. The serum level of thyroid hormones can also be transiently elevated either by aspiration of the thyroid [21], or by resection of a parathyroid adenoma without thyroidectomy [22]. The low thyroidal RAID might be explained by the destruction of the follicle around the nodule, the decreased serum level of TSH and/or increased iodine liberation from the thyroid.…”
Section: Discussionmentioning
confidence: 99%